Isolation and characterization of piceatannol producing bacteria from soil in Erzurum, Turkey: Biosynthesis of piceatannol from resveratrol - Koc, Taha Yasin; Gulluce, Medine; Yilmaz, Bilal; Karadayi, Mehmet (Cellular and Molecular Biology, 2024)
Piceatannol, resveratrol’s derivative, and a valuable polyphenol has managed to become one of the most remarkable candidate molecules for drug development research, with its high bioactive properties and higher stability. On the other hand, the very low amount of piceatannol in plants which are its natural source increases the cost and limits the commercialization possibilities of the product. To overcome this bottleneck, a limited number of studies have recently shown that it is possible to produce piceatannol from the resveratrol precursor much cheaper by regioselective hydroxylation catalyzed by bacteria isolated from the soil, and the search for new bacteria of similar nature in new ecosystems has gained popularity. The aim of our study, which was prepared within this framework, is the bacterial isolate with regioselective hydroxylation potential obtained as a result of selective isolation steps; determination of resveratrol hydroxylation potentials and piceatannol product yields, investigation of possibilities to increase piceatannol yield with optimization trials and identification of isolates with the highest yield. For this purpose, 200 bacterial isolates capable of resveratrol hydroxylation were obtained from soil samples taken from Erzurum (Turkey) and its surroundings by using selective media. In the continuation of the study; resveratrol hydroxylation trials were carried out with these isolates and 55 active isolates capable of producing piceatannol by regioselective hydroxylation were selected. Then, yield improvement studies of active isolates were carried out by using different carbon sources and optimizing the culture conditions. As a result, a culture collection was created by identifying the 6 most active bacterial isolates with commercialization potential using conventional and molecular methods. These are 4 Gram-positive (Rhodococcus sp., Rhodococcus erythropolis, Paeniglutamicibacter sp., Arthrobacter sp.) and 2 Gram-negative (Shinella sp., Ensifer adhaerens) bacterial isolates. As a result of the optimization studies, three of these isolates used phenol as a biocatalyst, while the other three increased the production yield of piceatannol by using 4-hydroxyphenylacetic acid.